Influence of root canal moisture on the penetration of TotalFill bioceramic sealer into the dentinal tubules: A confocal laser scanning microscopy study - Archika M Singh; Tarek M Elsewify; Walid S El-Sayed; Husam H Nuawafleh; Ranya F Elemam; Bassem M Eid (Wolters Kluwer Medknow Publications, 2024)
Introduction: Bioceramic (BC) sealers exhibit multiple desirable biologic and physical properties. The aim of this study was to evaluate the effect of root canal moisture on the depth of TotalFill BC sealer penetration into dentinal tubules at different levels using a confocal laser scanning microscope (CLSM). Materials and Methods: The manuscript of this laboratory study has been written according to preferred reporting items for laboratory studies in endodontology 2021 guidelines. Forty single-rooted extracted human premolars were decoronated using a low-speed diamond disc, followed by root canal preparation using nickel-titanium files under copious irrigation. The samples were randomly allocated for obturation into four groups n = 10 based on the sealer and root canal moisture status. Group A: TotalFill BC sealer in wet canal, Group B: TotalFill BC sealer in dry canal, Group C: AH Plus sealer in wet canal, and Group D: AH Plus sealer in dry canal. The roots were sectioned at three different distances from the apex. The root segments were examined using CLSM to measure the extent of sealer penetration into the dentinal tubules. The data underwent analysis through a three-way mixed ANOVA test, followed by post hoc assessments (P < 0.05). Results: In wet canals, the tubular penetration of TotalFill BC sealer was notably greater than that of AH plus, with a statistically significant difference. However, AH Plus sealer had a statistically significant tubular penetration in the dry canals compared to the wet. Greater sealer penetration was observed at 5 mm from the apex, followed by 3 mm, and the least penetration depth was found at 1 mm from the apex. Conclusions: The presence of root canal moisture and distance from the apex had a significant impact on the penetration of TotalFill BC sealer into the dentinal tubules.